The Representation of African Cultural Identity in Black Panther Film by Ryan Coogler (The Application of Stuart Hall’s Theory) - Shinta Sere; Muarifuddin Muarifuddin; Fina Amalia Masri (ELITE: Journal of English Language and Literature, 2020)
This study focuses on the analysis of The Representation of African Cultural Identity in Black Panther. This study aims to reveal the portrayal of African cultural identity in real life. In analyzing the data the writer used both library and media research related to this study, the writer applied a qualitative descriptive study as the method of this study. The source of data in this study Black Panther movie which is directed by Ryan Coogler and it was released in 2018. The data were collected through process of watching, pausing and interpreting then the writer analyses those data by using theory of Representation by Stuart Hall through constructionist approach. Black Panther movie became a medium to change the audience perspective about Africa. This movie shows the depiction of various kinds of cultural identity in Africa that can open the audience's thoughts about Africa. The results of this study indicate that the Black Panther movie has become a medium to provide a better perspective through the description of several elements related to African identity:Representation of African civilization through a symbol of vibranium, cultural ritual, traditional costume, African images through the character those elements are used by Ryan Coogler as director to develop a different perspective of Africa.